Differential effects therapy of Javanese-traditional (Karawitan instrumental) music and classical music in the first stage and second stage of childbirth - Santi, Mina Yumei; Arum, Dyah Noviawati Setya; Ismiyati, Atik; Siswati, Siswati; Wulansari, Mudayah Devit (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: Labor pain may induce maternal anxiety, interfere with uterine contractions, and prolong the birthing process. Music therapy is a non-pharmacological intervention known to mitigate both labor pain and anxiety. Objective: This study aimed to compare the effects of Javanese-traditional (Karawitan instrumental) and classical music therapies on anxiety, labor pain, and the duration of the first and second stages of labor.Methods: A randomized controlled trial was conducted involving 201 mothers undergoing normal labor at primary healthcare centers. Participants were assigned into three groups: Javanese-traditional music (Karawitan instrumental), classical music, and a control group practicing deep breathing. Interventions lasted 40 minutes. Anxiety was measured using the Spielberger State-Trait Anxiety Inventory, pain intensity with a visual analog scale, and labor duration through partograph analysis. Statistical tests included paired t-test, Wilcoxon signed-rank, Kruskal-Wallis, one-way ANOVA, and Mann-Whitney U testsResults: Both music interventions significantly reduced anxiety and pain within groups (p-value< 0.001). No significant difference in pain reduction was found between the two music groups during the first active phase (p-value= 0.108). Similarly, anxiety scores did not differ significantly between the music groups post-intervention (p-value= 0.956), though classical music showed a slightly greater reduction. Regarding labor duration, Javanese-traditional music was associated with a shorter first stage, while classical music significantly reduced the duration of the second stage (p-value= 0.000 and p-value= 0.035, respectively).Conclusions: Javanese-traditional (Karawitan instrumental) and classical music therapies are both effective in reducing maternal anxiety and labor pain while supporting labor progress. Javanese-traditional (Karawitan instrumental) music demonstrated greater effectiveness during the first stage, whereas classical music offered benefits in anxiety reduction and second-stage labor duration